Centralized Management Mechanism for Cell Outage Compensation in LTE Networks. (20th November 2012) - Wenjing, Li; Peng, Yu; Zhengxin, Jiang; Zifan, Li
Abstract : To mitigate the performance degradation induced by the cell outage, in this paper, a centralized cell outage compensation management mechanism and the corresponding workflow are proposed. Then a concrete algorithm named autonomic particle swarm compensation algorithm (APSCA) is proposed to generate the compensation scheme. The simulation results show that the proposed APSCA is effective to resolve the coverage problems induced by the outage. In the simulation scenario, almost 98.3% users that would otherwise be dropped will be served by the surrounding cells, and the block probabilities of the compensating cells are still kept on the accepted levels.